Genome-Wide SNP Discovery and Population Structure Analysis of 244 Indonesian Local Rice Accessions - Satrio, Rizky Dwi; Fendiyanto, Miftahul Huda; Nugroho, Satya; Hairmansis, Aris; Miftahudin (HAYATI Journal of Biosciences, 2026)
Single Nucleotide Polymorphism (SNP) markers are essential tools for the genetic management and breeding of rice, enabling precise characterization of genetic diversity. However, SNP datasets specifically developed for analyzing the population structure of Indonesian local rice remain limited. This study aimed to identify polymorphic SNP markers and analyze the lineage and population structure of 244 Indonesian local rice accessions. BAM files of these accessions were obtained from the 3K Rice Genome Project via the International Rice Informatics Consortium. High-quality SNPs were generated through variant calling and stringent filtering, followed by annotation and population analyses using IR64, DJ123, and Nipponbare as references. A total of 3,839,961 high-quality SNP loci were identified across the 12 rice chromosomes. Hierarchical clustering and principal coordinate analysis consistently grouped the accessions into three major clusters, corresponding to Indica, Japonica, and admixed groups. Population structure analysis confirmed two main subpopulations: Indica and Japonica, with Japonica further divided into Temperate and Tropical subgroups. Eleven accessions showed admixed ancestry. This study provides essential insights into the genetic diversity and population structure of Indonesian local rice, supporting genetic resource conservation, trait discovery, and breeding efforts.